(untitled) - Frodin, David G. (Cambridge, 2001)
This book provides a selective annotated bibliography of the principal floras and related works of inventory for vascular plants. The second edition has been completely updated and expanded to take into account the substantial literature of the late twentieth century, and features a more fully developed review of the history of floristic documentation.
Keywords: Botany,Thực vật học; Bibliography,Tài liệu tham khảo